Answer:
-10x + 1.5
Step-by-step explanation:
-2(5x-0.75)
-10x+1.5
hope it's helpful ❤❤❤❤❤❤
THANK YOU.
#
Answer:
(–19, 55)
Step-by-step explanation:
y = –3x – 2 equation 1
5x + 2y = 15 equation 2
using equation 1 in equation 2 we have:
5x + 2(–3x – 2) = 15
5x –6x – 4 = 15
-x = 15+4
x=-19
using equation 1:
y = -3(-19)- 2
y= 57-2
y= 55
Answer:
B. 4
Step-by-step explanation:
Determine the constant of variation for the direct variation given.
(0, 0), (3, 12), (9, 36)
A. 3
B. 4
C.12
Direct variation is given by:
y = kx
Where,
k = constant of variation
(3, 12)
x = 3; y = 12
y = kx
12 = k*3
12 = 3k
k = 12 / 3
k = 4
(9, 36)
x = 9; y = 36
y = kx
36 = k * 9
36 = 9k
k = 36 / 9
= 4
k = 4
Constant of the variation = 4
Answer:
A
Step-by-step explanation: